Identification and validation of poor prognosis immunoevasive subtype of muscle-invasive bladder cancer with tumor-infiltrating podoplanin+ cell abundance. (1st January 2020) - Zhou, Quan; Wang, Zewei; Zeng, Han; Zhang, Hongyu; Liu, Zhaopei; Huang, Qiuren; Wang, Jiajun; Chang, Yuan; Bai, Qi; Liu, Li; Zhu, Yu; Xu, Le; et al.
ABSTRACT: The choice of chemo- or immuno-therapy for muscle-invasive bladder cancer (MIBC) patients remains contentious. Podoplanin is newly identified as an immune checkpoint which intrigues us to explore the clinical significance and immunoregulatory role of tumor-infiltrating podoplanin + cells (PDPN + cells) in MIBC. A retrospective analysis of 259 MIBC patients from Zhongshan Hospital (n = 141) and Shanghai Cancer Center (n = 118) was conducted. A total of 406 MIBC patients from TCGA database were enrolled to investigate the relationship between PDPN and molecular characterization. We found that tumor-infiltrating PDPN + cell abundance indicated an inferior overall survival and recurrence-free survival. pT2 MIBC patients with PDPN + cell low infiltration could benefit more from adjuvant chemotherapy (ACT). Increased PDPN + cell infiltration was associated with diminished GZMB and TNF-α expression while correlated with expanded PD-1, PD-L1, LAG-3 and TIM-3 expression and tumor-promoting regulatory T cell and M2 macrophage infiltration. Tumors with high PDPN mRNA expression mainly presented luminal-infiltrated and basal-squamous subtypes (2017 TCGA classification) or stroma-rich and Ba/Sq subtypes (consensus classification). Elevated PDPN mRNA expression was associated with less FGFR3 activation signature and more T-cell-inflamed signature and EGFR activation signature. In conclusion, tumor-infiltrating PDPN + cells could be applied as an independent prognosticator for clinical outcome and a predictive biomarker for suboptimal ACT responsiveness, which was also associated with immunosuppressive contexture infiltration. Intratumoral PDPN expression had a correlation with MIBC molecular classification and therapy-related signatures. The novel immune checkpoint PDPN should be considered as a possible immunotherapeutic target for MIBC.